A modified two-stage method for combining the aggregate-data and individual-patient-data in meta-analysis - Nik Idris, Nik Ruzni; Misran, Nurul Afiqah (Asian Network for Scientific Information, 2015)

(untitled)
The objective of this study is to ascertain the efficacy of the existing two-stage method for combining the Aggregate Data (AD) and Individual Patient Data (IPD) studies in meta-analysis and to introduce some modifications to the existing two-stage method for combining the these studies. We evaluated the effects of these modifications on the estimates of the overall treatment effect and investigated the influence of the number of studies included in the meta-analysis, N and the ratio of AD: IPD on these estimates. We used Percentage Relative Bias (PRB), Root Mean Square Error (RMSE) and coverage probability to assess the overall efficiency of these estimates. The results revealed that the current method for combining the AD:IPD studies exhibit rather poor coverage probability. We showed that the proposed methods had been able to improve the coverage probability by more than 40%, while maintaining the level of bias at par to their existing counterparts. These findings demonstrated the significance of proper technique for combining these studies in order to obtain better overall estimates, which is crucial for reliable overall conclusions.